Immunostimulating Effect of Levamisole on Spleen and Head-Kidney Leucocytes of Rainbow trout (Oncorhynchus mykiss, Walbaum 1792) - Seker, Engin; Ispir, Unal; Dorucu, Mustafa (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
An in vitro cultivation method for spleen and head kidney organ section were used to investigate the effects of levamisole on the immune response. After 10 days of culture with 10 mu g/ml, 50 mu g/ml and 100 mu g/ml or no levamisole in the culture media, the non specific defense reaction were measured by glass-adherent NBT (nitroblue tetrazolium) positive cells activation and phagocytic activity. Elevation in phagocytic activity was found for 10 mu g/ml and 50 mu g/ml levels of levamisole (P < 0.001), but no differences were found at levels of phagocytic activity in between 100 mu g/ml levamisole groups and control groups (P > 0.05). In the spleen and head kidney leucocytes, increased response to levamisole was shawn for all doses in the glass-adherent NBT positive cells activation.
Keywords: Levamisole; Immunomodulation; Rainbow trout; Immunity; Head-kidney; Spleen